PELATIHAN MENULIS KOMENTAR SINGKAT, PADAT DAN TEPAT DALAM MERESPON SEJUMLAH ISU VIRAL DI MEDIA SOSIAL DIKALANGAN SANTRI DKM MASJID AR-RAHMAH - Wulan Muhariani; Bobby Octavia Yuskar; Riastri Novianita; Athiy Dina Rosihana; Karina Kharisma Noviana; Elsa Sarah Tioma Siburian; Welhelmina Dethan (Yayasan Education and Social Center, 2023)
Nowadays, perhaps everyone uses media to carry out activities, especially activities related to communication between one individual and another individual. With media, it will be easier for everyone to carry out daily activities. Therefore, the definition of media can be said to be very broad, for you as a teacher you will definitely determine the appropriate learning media for your students. Not only that, the media which is more often used as an intermediary for communication is often used by workers or even political officials who want to nominate themselves. The media that often appear during the Indonesian democracy party are usually better known as political communication media. So, don't be surprised if during the Indonesian democracy party there will be a lot of information from various media containing only political issues or facts. Through the technological media revolution, the distance will indeed feel very close. The technological media revolution, as the fourth wave of development in world society, has led to a world that is truly vast and seems to have no distance